Kualitas Pelayanan Dokumen Perpindahan Penduduk di Kelurahan Pacarkeling Kota Surabaya - Nayani Alya Aquila Muzdalifah; Sri Wibawani (IAI Nasional Laa Roiba Bogor, 2024)
The government is obliged to provide good services in fulfilling the wants and needs of the community as stated in Undang-Undang Number 25 of 2009 concerning public services. Population administration services are one form of government public services with implementation at the village office in population administration services. The presence of the Klampid New Generation application is to assist the community in submitting population administration applications, one of which is the transfer service. In reality, several problems were found in population administration services. The existence of this research aims to analyze the quality of service of population transfer documents in Pacarkeling Village, Surabaya City using descriptive qualitative research methods with data analysis techniques referring to the Miles and Huberman model, namely analyzing data, namely data reduction, data presentation, and conclusion drawing and data collection techniques through interviews, documentation, observation, and literature study. This research uses five dimensions of public service quality theory according to Parasuraman, Zeithaml, and Berry, namely 1) Tangible, 2) Reliability, 3) Responsiveness, 4) Assurance, and 5) Empathy. The results showed that the population transfer service in Pacarkeling Village in terms of service quality can be said to be good.